PEMAHAMAN MAHASISWA ARSITEKTUR UNIVERSITAS FLORES TENTANG IMPLEMENTASI MERDEKA BELAJAR KAMPUS MERDEKA - Maria Tensiana Tima; Ernesta Leha; Silvester M Siso (Program Studi PGSD Universitas Flores, 2023)
The Independent Learning of the Independent Campus (MBKM) which was launched by the Ministry of Education, Culture, Research and Technology was the answer to the demands of the world of work today and in the future. This study aims to determine the students' understanding of the architectural study program at the Faculty of Engineering, University of Flores regarding the implementation of the independent learning policy on an independent campus (MBKM). This study uses a survey method conducted on all students of the architectural study program, totaling 238 people by filling out the link on SPADA DIKTI. Data analysis was carried out using a qualitative descriptive method. The results showed that 14% of students in the Architecture study program did not know anything about the content of the MBKM policy, 42% knew a little, 31% knew most of the content of the policy and 13% knew the policy as a whole. However, 77% of students stated that they were very interested in the MBKM program and 74% were very interested in recommending the program to their relatives or colleagues.